Cortical Microinfarcts and White Matter Connectivity in Memory Clinic Patients - Ferro, Doeschka; Heinen, Rutger; de Brito Robalo, Bruno; Kuijf, Hugo; Biessels, Geert Jan; Reijmer, Yael (Frontiers in Neurology, 2019)
Background and purpose: Cerebral microinfarcts (CMIs) are associated with cognitive impairment and dementia. CMIs might affect cognitive performance through disruption of cerebral networks. We investigated in memory clinic patients whether cortical CMIs are clustered in specific brain regions and if presence of cortical CMIs is associated with reduced white matter (WM) connectivity in tracts projecting to these regions. Methods: 164 memory clinic patients with vascular brain injury with a mean age of 72 ± 11 years (54 % male) were included. All underwent 3 tesla MRI, including a diffusion MRI and cognitive testing. Cortical CMIs were rated according to established criteria and their spatial location was marked. Diffusion imaging-based tractography was used to reconstruct WM connections and voxel based analysis (VBA) to assess integrity of WM directly below the cortex. WM connectivity and integrity were compared between patients with and without cortical CMIs for the whole brain and regions with a high CMI burden. Results: 30 patients (18%) had at least 1 cortical CMI [range 1- 46]. More than 70% of the cortical CMIs were located in the superior frontal, middle frontal and pre- and postcentral brain regions (covering 16% of the cortical surface). In these high CMI burden regions, patients with cortical CMIs tended to have impaired WM connectivity (p=.071), however this trend disappeared after correction for conventional neuroimaging markers of vascular injury. WM connectivity in the whole brain and WM voxels directly underneath the cortical surface did not differ between patients with and without cortical CMIs. Conclusion: Cortical CMIs displayed a strong local clustering in highly interconnected frontal, pre- and postcentral brain regions. Nevertheless, WM connections projecting to these regions were not disproportionally impaired in patients with compared to patients without cortical CMIs. Alternative mechanisms, such as focal disturbances in cortical structure and functioning, may better explain CMI associated cognitive impairment.